The role of organizational networking capabilities and agile leadership on organizational performance through dynamic managerial capabilities with moderating professional capabilities and dynamic organizational culture - Kholid; Suyanto, Bagong; Lestari, Yetty Dwi (International Journal of Innovative Research and Scientific Studies, 2025)
Education in Indonesia faces great challenges in adjusting to the demands of the times. The development of the industrial and business world is moving faster than the readiness of human resources produced by the education system. This study aims to analyze the role of Organizational Networking Capabilities and Agile Leadership on Organizational Performance through Dynamic Managerial Capabilities with the Moderation of Professional Capabilities and Dynamic Organizational Culture. This study uses a quantitative approach, employing a survey method. In this study, theoretical and empirical studies were conducted to formulate problems, followed by hypotheses. After collecting field data, calculations were performed using MPlus, and the results were used to analyze the dissertation. The sampling technique utilized a questionnaire in one stage from 75 schools, consisting of 375 school leaders and 375 senior teachers or certified teachers in Greater Surabaya and Greater Malang. From the results of hypothesis testing, it was found that Organizational Networking Capabilities has a significant effect on Dynamic Managerial Capabilities (H1) and Organizational Performance (H4), as well as through the mediation of Dynamic Organizational Culture (H8). Agile Leadership has no significant effect on Dynamic Managerial Capabilities (H2) or Organizational Performance (H5), but it has a significant effect on Organizational Performance through the mediation of Dynamic Organizational Culture (H9). Agile Leadership, moderated by Professional Capabilities, has a significant effect on Dynamic Managerial Capabilities (H3). Dynamic Managerial Capabilities has no significant effect on Organizational Performance (H6), but its effect becomes significant when moderated by Dynamic Organizational Culture (H7). Thus, some hypotheses are supported while others are not, indicating the important role of organizational capabilities, agile leadership, and organizational culture in organizational performance.